Sonatinas for the piano: Op. 36, 37, 38 - CLEMENTI, Muzio (G.Schirmer, Inc., 1893)
Di dalam buku ini terdapat 12 lagu:Sonatina, Op.36, No.1; Sonatina, Op.36, No.2; Sonatina, Op.36, No.3; Sonatina, Op.36, No.4; Sonatina, Op.36, No.5; Sonatina, Op.36, No.6; Sonatina, Op.37, No.1; Sonatina, Op.37, No.2; Sonatina, Op.37, No.3; Sonatina, Op.38, No.1; Sonatina, Op.38, No.2; Sonatina, Op.38, No.3